(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Vocational education is an important aspect of the overall education system in India and has been given renewed emphasis through the Samagra Shiksha initiative. This article critically analyses the implementation of vocational education under the Samagra Shiksha program with a focus on its impact on students, schools, and the economy. The study finds that while the initiative has led to an increase in the number of vocational courses offered in schools, there are still major gaps in the quality of education and lack of support for students in finding employment after graduation. Additionally, the article highlights the need for more effective measures to improve the delivery and outcomes of vocational education in the country. Overall, the article provides valuable insights for policy-makers, educators, and stakeholders in the field of vocational education.